Skin Prick Test Versus Phadiatop as a Tool for Diagnosis of Allergic Rhinitis in Children. Issue 1 (January 2021) - Traiyan, Sasiwimon; Manuyakorn, Wiparat; Kanchongkittiphon, Watcharoot; Sasisakulporn, Cherapat; Jotikasthira, Wanlapa; Kiewngam, Potjanee; Kamchaisatian, Wasu; Benjaponpitak, Suwat
Background: Skin prick test (SPT) or Phadiatop, a multi-allergen IgE screening test, was used as a tool for detecting aeroallergen sensitization. Objective: To compare SPT and Phadiatop as a tool for diagnosis allergic rhinitis (AR) using the nasal provocation test (NPT) as a comparative standard. Methods: Children aged 5-18 years with rhinitis symptoms more than 6 times in the past year were enrolled. SPT to 13 common aeroallergens, serum for Phadiatop, and NPT to Dermatophagoides pteronyssinus (Der p) were performed. NPT to mixed cockroach (CR) were performed in children who had CR sensitization and negative NPT to Der p. Children who had a disagreement between the result of SPT and Phadiatop or having negative results were evaluated for specific IgE (sIgE) to common aeroallergens. Results: One hundred-forty children were enrolled with the mean age of 9.8 ± 3 years, 56% were male. Of 92 children (65.7%) with positive SPT to any aeroallergens, 88 children (95.6%) were sensitized to house dust mite (HDM). NPT showed positive results in 97 children (69.3%). Of 48 children who showed negative SPT, 4 children (8.3%) had sIgE to aeroallergens but NPT was positive in 1 child. Eighty-eight children (62.9%) had positive tests for Phadiatop and 4 (4.5%) of them had negative results for NPT to Der p. Among 52 children who had negative results for Phadiatop, 4 children (7.6%) had sIgE to aeroallergens but NPT was positive in 2 children (3.8%). SPT and Phadiatop showed 94.2% agreement: with Kappa 0.876, p < 0.001. Using NPT as a comparative standard for diagnosis for AR, SPT showed a sensitivity of 89.6% and specificity of 88.3% and Phadiatop provided the sensitivity of 88.6% and specificity of 95.3%. Conclusions: SPT to aeroallergen and Phadiatop have good and comparable sensitivity and specificity for the diagnosis of AR in children.